Solar irrigation/drip irrigation coupled with artificial recharge of groundwater technology: IPSR Innovation Profile - Magombeyi, Manuel Simba; Owusu, Seth; Gyasi-Abrokwah, Bernard (2022)
The innovation uses the site suitability mapping for implementing the Aquifer Storage and Recovery (ASR) method called Bhungroo Irrigation Technology (BIT) and solar irrigation pumping to smallholder irrigation schemes that use groundwater and surface water in the Inkomanti-Usuthu Catchment Management Area in South Africa. The ASR /BIT uses one borehole to recharge the aquifer during the wet season and abstract water from the same borehole during the dry season. This resulted in increased irrigation water availability and reduced energy use from grid electricity and fuel pumps, thereby increasing farm profit. Energy use for irrigation contributed 50-70% of the total farming expenses. Successful implementation of the BIT and solar irrigation pumping at a site requires the delineation of suitable areas based on scientific, natural parameters and expert judgment.